Pengembangan Dashboard Interaktif Indeks Desa Membangun(IDM) Berbasis Web Provinsi Sumatera Selatan - Dwi Novanni, Windri; Nasir, Muhammad (PPPM Institut Teknologi Pagar Alam, 2026)
The Village Development Index (IDM) is an important instrument for assessing the level of development and independence of villages in Indonesia. Therefore, data covering social, economic, and environmental aspects need to be presented visually and informatively for easy understanding by various stakeholders. The system development used the Waterfall method, which includes sequential stages of needs analysis, design, implementation, testing, and maintenance. A dashboard was built to present data in the form of tables, graphs, and interactive maps. In addition, this dashboard is intended to be integrated and displayed on the